The time-limited influence of sentential context on function word identification - van Alphen, P; McQueen, J M (Journal of experimental psychology. Human perception and performance, 2001)
Sentential context effects on the identification of the Dutch function words te (to) and de (the) were examined. In Experiment 1, listeners labeled words on a [t inverted e]-[d inverted e] continuum more often as te when the context waste biased (Ik probeer [? inverted e] schieten [I try to/the shoot]) than when it was de biased (Ik probeer [? inverted e] schoenen [I try to/the shoes]). The effect was weaker in slower responses. In Experiment 2, disambiguation began later, in the second word after [? inverted e]. There was a weak context effect only in the slower responses. In Experiments 3 and 4, disambiguation occurred on the word before [? inverted e]: There was no context effect when one set of sentences was used, but there was an effect (larger in the faster responses) when more sentences were used. Syntactic processing affects word identification only within a limited time frame. It appears to do so not by influencing lexical access processes through feedback but, instead, by biasing decision making.